Three blind mice : a novel - McBain, Ed, 1926-2005 (Arcade Pub., 1990)
Jessica's accused rapists were acquitted and Stephen, her husband, threatened to take justice into his own hands. After they are found murdered, she turns to Matthew Hope to defend her husband.